2014
DOI: 10.1371/journal.pone.0096238
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Activation of Notch3 Amplifies the Proliferative Potential of Rhabdomyosarcoma Cells

Abstract: Rhabdomyosarcoma (RMS) is a pediatric myogenic-derived soft tissue sarcoma that includes two major histopathological subtypes: embryonal and alveolar. The majority of alveolar RMS expresses PAX3-FOXO1 fusion oncoprotein, associated with the worst prognosis. RMS cells show myogenic markers expression but are unable to terminally differentiate. The Notch signaling pathway is a master player during myogenesis, with Notch1 activation sustaining myoblast expansion and Notch3 activation inhibiting myoblast fusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Intriguingly, the transcriptional co-activator YAP1 (but not its homolog TAZ, encoded by WWTR1 ) (Fig.1B) and the Notch pathway readout genes HEY1 and HES1 (Fig.1C) were also increased in both cell lines, suggesting YAP and Notch expression may support stemness. To gain insight into the mechanism of increased Notch pathway activation, we investigated the expression of Notch ligands and receptors previously implicated in eRMS tumorigenesis (7,10,13,59), and found increased expression of the Notch ligands JAG1 and DLL1 (Fig.1D) and the Notch receptors NOTCH1 and NOTCH3 (Fig.1E). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the transcriptional co-activator YAP1 (but not its homolog TAZ, encoded by WWTR1 ) (Fig.1B) and the Notch pathway readout genes HEY1 and HES1 (Fig.1C) were also increased in both cell lines, suggesting YAP and Notch expression may support stemness. To gain insight into the mechanism of increased Notch pathway activation, we investigated the expression of Notch ligands and receptors previously implicated in eRMS tumorigenesis (7,10,13,59), and found increased expression of the Notch ligands JAG1 and DLL1 (Fig.1D) and the Notch receptors NOTCH1 and NOTCH3 (Fig.1E). …”
Section: Resultsmentioning
confidence: 99%
“…Notch signaling is upregulated in several human cancer types (reviewed in (9)). In eRMS, Notch receptors 1–4, ligands JAG1 and DLL1, the transcription factor RBPJ, and the Notch target genes HEY1 and HES1 have been found upregulated (7,1014). Functionally, Notch signaling promotes eRMS proliferation and self-renewal (7,15), inhibits myogenic differentiation (7), and increases eRMS cell mobility and invasiveness (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of these targets reduced proliferation as previously shown. 11, 20, 24, 34, 35 This finding suggests that single targets and even a subset of targets are insufficient to induce differentiation to the extent induced by miR-206 overexpression. Thus, target identification collectively is a key to understanding the mechanism of miR-206-induced differentiation in RMS further suggesting the ‘1 miRNA-1 target' model to be insufficient to explain complex phenotypes induced by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…20 NOTCH signaling is also increased in RMS and NOTCH inhibition promotes RMS differentiation. 34, 35, 36 The paired-box transcription factors, PAX3 and PAX7, are expressed in embryonic muscle progenitors and function upstream of Myf5 and MyoD1 to promote myoblast and satellite cell proliferation and self-renewal. 7 PAX3/PAX7 are normally downregulated in myogenic differentiation and their exogenous overexpression inhibits differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Notch3 is overexpressed in rhabdomyosarcoma cell lines compared with normal myoblasts and has been shown to induce proliferation via a Hes1‐dependent mechanism . Downregulation of Notch3 in vitro resulted in increased differentiation of alveolar rhabdomyosarcoma cells and a reduction in cellular proliferation . It has been suggested that osteosarcoma maintains an undifferentiated state by depressing of Notch3 and its downstream target Hes5 [147].…”
Section: Connective Tissue Tumorsmentioning
confidence: 99%